Mechanism of Immune Response Through mRNA/miRNA Effect in Vascular Dysfunctions - Jiang, Hong; Ali, Hassam; Iftikhar, Hassah Batool (Cardiology and Cardiovascular Medicine, 2018)
With the aim of understanding the socioeconomic burden of autoimmune diseases, attenuating ACS introduce the phenomenon of the immunological regulation system provoking all stages of predisposing lesions criticizing the arousal of prognostic metabolic role at cellular biogenesis. The basic methodologies of repairs focus on the significance of mRNA/miRNA triggering the kinetics of pharmacodynamics obstacles at CVD mortality, identify the systematic therapeutics of exertions in the miRNAs of 21, 29, 23, 27, 24, 126, 143 and 145 insights the signaling of platelet aggregation associates the gene expressions in the form of supportive biomarker targets.